Tribute to Lois Ehrenburg at Jon Jon's - Watkins, Howard::::::::: (1981)
Randy Walsh playing harmonica and guitar and singing at portable microphone; Margaret Sharp, Karen Humphrey, Dale Doig, Mary Nelson watching